Development of Computer Based Diagnostic Test for Student Misconception on Material Temperature and Heat - Abbas, Muhammad Luqman Hakim (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2020)
Misconception diagnostic tests are rarely carried out by lecturers in lectures because of the length of time needed to make test instruments and data analysis to be able to provide immediate feedback. The purpose of this study was to produce a Computer Based Diagnostic Test Misconception program for students in physics on temperature and heat. The research design used was the modified Borg and Gall Research and Development (R & D). This research was conducted at Tulungagung IAIN by involving 10 students of educations Physics The instrument for data collection is in the form of a validator questionnaire, and a product development trial questionnaire. The research data includes quantitative data in the form of evaluating validators and questionnaires from the trial results, as well as qualitative data in the form of comments and suggestions given by validators and students. The results show that the development program is feasible to use based on expert validation with very feasible categories and supported by student responses / comments in good categories. The computer based diagnostic test misception program produced has four main parts, namely diagnostic tests, diagnostic test results, discussion of questions, and remedial in the form of remedial material. The results of the analysis of effectiveness tests can be concluded that computer based diagnostic test misconseption programs can improve students' conceptual understanding and be able to reduce student misconceptions in temperature and heat material.